Analisis Pengaruh Literasi Keuangan Dalam Penggunaan Digital Payment Terhadap Perilaku Konsumen Cafe Kopi Api Makassar. - Atia Kirana W; Nurdjanna Fadjrin Uluputty (Jurnal Mirai Management, 2023)
This study aims to analyze the effect of financial literacy on consumer behavior in using digital payments at Cafe Kopi API Makassar. The method used is a survey by distributing questionnaires to 100 respondents who are regular customers of the cafe. The independent variables in this study are financial literacy and use of digital payments, while the dependent variable is consumer behavior. Data was collected through a questionnaire which included questions about the level of understanding of financial concepts and the frequency of use of digital payments by respondents. Data analysis and hypothesis testing were carried out using multiple linear regression analysis techniques. The results of the analysis show that financial literacy has a significant impact on consumer behavior in using digital payments at Cafe Kopi API Makassar. Respondents who have a higher level of financial literacy tend to use digital payments more actively and choose it as the main payment method when visiting the cafe. These findings show the importance of increasing financial literacy for consumers so that they can properly understand the benefits and risks of using digital payments. In this case, Cafe Kopi API Makassar can provide financial education to its customers to increase their understanding of how to use digital payments wisely. It is hoped that the results of this research can provide input for other cafes to increase customer acceptance and satisfaction through the effective implementation of digital payments, as well as strengthen awareness of the importance of financial literacy in consumer decision making. Keywords: Financial Literacy, Digital Payment, Consumer Behavior.